Implants for surgery - Components for partial and total knee joint prostheses - Part 1: Classification, definitions and designation of dimensions (ISO 7207-1:2007, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Fazan, Fazilah; et al. (Department of Standards Malaysia, 2010)
ISO 7207-1:2007 classifies femoral, tibial and patellar components for knee joint prostheses in which the bearing surfaces of one or more compartments of the knee are replaced. It also gives definitions of components and the designation of dimensions.